Uso de capas PML en el Modelado del Campo Acústico de un Transductor HIFU Cóncavo - García, Juan Carlos; Martínez-Valdez, R.; Vera, A.; Leija, L. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
High intensity focused ultrasound (HIFU) as a non-invasive technique is under study due to its application in rehabilitation and as oncological therapy. High intensity pressure in a millimetric space generates high acoustic intensity that produces an ablation temperature (> 60 °C). For treatment planning in cancer therapy and systems characterization, it is usual to use computational modeling. Finite Element Method (FEM) is a common tool used to solve acoustic fields produced by HIFU transducers. However, the computational cost could represent an issue; therefore, it is necessary to simplify the model to try obtaining an approximate solution that can be validated. In this work, modeling of the acoustic propagation of a HIFU transducer was made by means of a perfectly absorbing artificial layer named perfectly matched layer (PML). The methodology consisted in the proposal of a minimum distance to place this layer from the region of interest, which keeps a relation to the focal zone. The results showed a decrease in the number of elements used for the solution; consequently, there was a reduction of more than twice the simulation time compared to a reference model. The simulations were validated with experimental acoustic pressure measurements along the propagation axis where the maximum pressure was located at 97 mm. For our model, the maximum pressure reached was found at 97.165 mm, whereas for the other models there was an increase in distance up to 0.62 mm.